Long-term Neurodevelopmental and Growth Outcomes of Necrotizing Enterocolitis Among Preterm Infants: A Systematic Review - Maria Margarita Oratmangun; Mega Hasanul Huda; Yeni Rustina; Dessie Wanda (PT.Mantaya Idea Batara, 2026)
Background: Preterm infants with necrotizing enterocolitis (NEC) are at increased risk of mortality, severe morbidity, and adverse long-term neurodevelopmental and growth outcomes. Objective: This systematic review aimed to identify and synthesize evidence on the long- term impact of NEC on neurodevelopmental and growth outcomes in preterm infants, including differences between medical and surgical NEC. Methods: The review adhered to PRISMA 2020 guidelines, with literature searches conducted in ScienceDirect, Sage Journals, ProQuest, PubMed, Scopus, and Wiley for studies published between 2015 and 2025. Study quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. From a total of 2,055 articles identified, supplemented by citation tracking, 10 studies were included in this review. Result: The findings indicate that NEC survivors have a higher risk of neurodevelopmental impairment, including lower cognitive, motor, and language scores, behavioral problems, and an increased risk of cerebral palsy, particularly among infants requiring surgical intervention. Regarding growth outcomes, NEC survivors demonstrated persistent deficits in weight, height, and head circumference that may extend into school age and adolescence. Several studies also reported reduced fat mass and decreased bone mineral density in early childhood. Surgical NEC was consistently associated with poorer outcomes than medical NEC. Conclusion: The findings indicate that NEC in preterm infants has significant long-term consequences for neurodevelopment and growth. Comprehensive multidisciplinary follow- up, family empowerment, standardized developmental screening, nutritional optimization, and risk-based early intervention are crucial for improving long-term outcomes and quality of life among NEC survivors.